Determination of bisphenol A: Old problem, recent creative solutions based on novel materials. Issue 6 (15th October 2020) - Huelsmann, Ricardo Dagnoni; Will, Camila; Carasek, Eduardo
Abstract: Bisphenol A is a synthetic compound widely used in industry, in the production of polycarbonate, epoxy resins, and thermal paper, among others. Its annual production is estimated at millions of tons per year, demonstrating its importance. Despite its wide application in various everyday products, once in the environment (due to its disposal or leaching), it has high toxicity to humans and animal life, and this problem has been well known for years. Given this problem, many researchers seek alternatives for its monitoring in matrices such as natural water, waste, food, and biological matrices. For this, new advanced materials have been developed, characterized, and applied in creative ways for the preparation of samples for the determination of bisphenol A. This article aims to present some of these important and recent applications, describing the use of molecularly imprinted polymers, metal and covalent organic frameworks, ionic liquids and magnetic ionic liquids, and deep eutectic solvents as creative solutions in sample preparation for the long‐standing problem of bisphenol A determination.